Is 1 always less than 2 in Norwegian tonal accents? - Kristoffersen, Gjert (Franz Steiner Verlag GmbH, Stuttgart, 2006)
As in Swedish, a tonal accent distinction is found in most Norwegian dialects. The distinction is dependent on primary stress, so that any primary stress will be pronounced with one of the two melodies that manifest the accent distinction. The phonetic manifestation of the melodies will vary with dialect, but two main groups can be identified. The East Norwegian type is found in the central and eastern part of Southern Norway. Here, accent 1 is characterized by a low tone relatively late in the stressed syllable, while accent 2 consists of a high tone early in the stressed syllable, falling to a low tone on the following syllable. The West Norwegian type, spoken in the western and southern part of Southern Norway, and in all dialects of Northern Norway where the accent distinction is present, is characterized by a high tone on the stressed syllable in accent 1, and a high tone on the following syllable in accent 2. In recent analyses of West Norwegian tone a low tone is posited as well on the stressed syllable in accent 2. The evidence for this low tone will be the topic of the present chapter.